Formation of the System of Legal Protection of Intellectual Property in Ukraine and Modern Problems of Its Development - Myronenko, Nataliia (Teisė, 2022)
The article consistently identifies the stages of formation of legislation in the field of intellectual property and provides a general description of them. The impact on its formation of EU legislation, the TRIPSS Agreement and the Association Agreement between Ukraine and the EU is determined. Theoretical approaches to determining the essence of codification of legislation as a legal phenomenon are analyzed. The features of codification as an activity and as a result are distinguished. The experience of foreign countries in the codification of legislation in the field of intellectual property and different approaches to determining the type of codification act are analyzed. The stages of codification of legislation in the field of intellectual property are singled out and their content is determined.
Keywords: intellectual property; codification; legislation; doctrine of intellectual property law; codification act